THE ROLE OF JOURNALIST ORGANIZATIONS IN IMPROVING THE PROFESSIONALISM AND CREDIBILITY OF JOURNALISTS IN ACEH - Anhar Fazri; Nurul Bayani; Dony Arung Triantoro; Jalaluddin (Kinesik, 2022)
The journalist profession can help the public get information quickly and easily. However, there is public distrust of the circulating news. One of the reasons is the credibility of journalists who are considered by the public to be declining. For journalists, this phenomenon is very paradoxical and not easy. However, like other cities in Indonesia, Aceh already has a journalist organization known as the Indonesian Journalists Association (PWI). Therefore, this study seeks to examine the role of Acehnese journalist organizations in improving journalistic professionalism. To find out how the role of journalist organizations in improving the professionalism of journalists, this study uses a qualitative approach with data collection techniques in the form of interviews and observations. Then the research data were analyzed using social responsibility theory (SR-Theory). Several programs initiated by this organization include training in journalistic code of ethics, professional responsibility for journalism, writing training, reportage training, editing workshops, photographers, videographers, and competency tests for members, as well as journalism socialization to schools in Aceh. On the other hand, the existence of this organization can be a legal protection for journalists.